THE USE OF PHONEMES IN SYNTAX IN TEACHING ARABIC AS A SECOND LANGUAGE/ ØªÙˆØ¸ÙŠÙ Ø§Ù„ÙÙˆÙ†ÙŠÙ…Ø§Øª ÙÙˆÙ‚ Ø§Ù„ØªØ±ÙƒÙŠØ¨ÙŠÙ‘Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¹Ø±Ø¨ÙŠÙ‘Ø© Ù„ØºØ© Ø«Ø§Ù†ÙŠØ© - Al-Hassan Seedah, Abdulhakeem Abdul Kaleg (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The study deals with the phonemes on syntax and their employment in the teaching of Arabic to non-Arabic speakers. The study aims at explaining how these phonemes are used in the teaching of Arabic as a second language. The study also aims to explain the role played by these secondary phonemes in communicating the Arabic language to an optimal level of sound; Acoustic sounds are not isolated but need to be viewed at the level of composition as well. Moreover, to reach the desired goals, the researcher divided the research into two sections and contained each of these sections on the axes.The first topic came in terms of theoretical framework, where the researcher talked about the importance of the audio lesson for the Arabic learner a second language, and the second axis of the definition of the phonemes above the structure of the lesson and attention, the practical side of the study was divided into axes, namely: Â The use of algebra in the teaching of Arabic as second language, the use of toning in teaching